A Numerical Analysis Of Transient Flow Past Road Vehicles Subjected To Pitching Oscillation - Tsubokura, Makoto; Cheng, See Yuan; Nakashima, Takuji; Nouzawa, Takahide; Okada, Yoshihiro (Elsevier Ltd, 2011)
Conventionally, the pitching instability of road vehicles has been controlled mechanically through the application of suspension systems. The present study demonstrates how unsteady aerodynamics can be exploited for such control by properly configuring vehicle body shapes. To discern the effect of unsteady aerodynamics on road vehicle stability, large eddy simulation has been conducted to simulate the flow past simplified vehicle models. Forced-sinusoidal-pitching oscillation was imposed on the models during the simulation to probe their dynamic responses. Numerical results were compared with wind tunnel measurements for validation, and good agreement is attained. Unsteady flow structures above the rear section of the vehicles were found to significantly affect their pitching stability. Depending on the vehicle body shape configurations, the induced aerodynamic force tended to either enhance or restrain the vehicles’ pitching instability.